2023
DOI: 10.7759/cureus.39764
|View full text |Cite
|
Sign up to set email alerts
|

Early Initiation of Vestibular Therapy Following Sports-Related Concussions: A Retrospective Cohort Study

Abstract: Background: Vestibular dysfunction is common following sports-related concussions (SRC). Within the current practice, it is theorized that patients with vestibular dysfunction as sequelae of sports-related concussion have a prolonged recovery time compared to those without vestibular dysfunction.Study method: A retrospective, cohort investigation of 282 subjects with sports-related concussions with vestibular dysfunction was conducted at The Sports Medicine Concussion Clinic, Duke University. The primary endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…For example, an individual who sustained a grade 3 concussion once could potentially have higher balance decrements compared to an individual who had two grade 1 concussions. Recent evidence indicates that early initiation of clinical interventions, including vestibular therapy following concussion, positively impacted the recovery time [28,29] and functional outcomes [30]. Moreover, in the current study, the timing of concussion(s) was not taken into consideration.…”
Section: Effects Of Multiple Concussions On Postural Stabilitymentioning
confidence: 89%
See 1 more Smart Citation
“…For example, an individual who sustained a grade 3 concussion once could potentially have higher balance decrements compared to an individual who had two grade 1 concussions. Recent evidence indicates that early initiation of clinical interventions, including vestibular therapy following concussion, positively impacted the recovery time [28,29] and functional outcomes [30]. Moreover, in the current study, the timing of concussion(s) was not taken into consideration.…”
Section: Effects Of Multiple Concussions On Postural Stabilitymentioning
confidence: 89%
“…As the timing of full recovery is still unclear, balance and gait assessment should be a part of the concussion assessment. Moreover, since disruption of the vestibular structure and function is the major reason for the postural issues following concussions, vestibular rehabilitation therapy (VRT) could improve the recovery time [28,29]. Additionally, it has been shown that when VRT is combined with cervical therapy, it allows the athletes to be able to return to play within eight weeks of their concussion [29].…”
Section: Effects Of Timing Of Concussions On Postural Stabilitymentioning
confidence: 99%
“…Optimal prescription and efficacy of VRT in patients with concussion is still a work in progress (Murray et al 2017 ). However, there is good evidence to support that earlier vestibular intervention for concussion has a direct relationship on earlier recovery and return to sport (Ferry et al 2023 ). There is evolving evidence to show that individually tailored multimodal interventions including cervical, vestibular and/or oculomotor therapies provide a faster return to sport and clinical improvement, especially in those with persistent symptoms (Galeno et al 2022 ; Reid et al 2022 ; Reneker et al 2017 ; Schneider et al 2014) and that sub-symptom aerobic exercise lowers symptom scores (Reid et al 2022 ), but we need larger samples to validate this.…”
Section: Our Understanding Of Concussion Todaymentioning
confidence: 99%